Understanding Enterprise Architecture: Blueprinting Scalable and Compliant IT Landscapes - Mohan, Vinod Nagarahalli (International Journal of Computing and Engineering, 2025)
Enterprise architecture serves as a pivotal structure for uniting technological systems with institutional aims in today’s swiftly changing digital landscape. Its core concepts, often unclear to technical staff and corporate leaders, are fundamental to thriving operations. This article highlights indispensable elements—flexible system designs, fluid system connections, diligent data oversight, and strict regulatory alignment—necessary for effective execution. It stresses how well-planned architectural frameworks propel institutional advancement, link diverse technological environments, and sharpen responsiveness to market shifts. System planners, connectivity specialists, and compliance stewards collaborate to maintain unity across business processes, software tools, and technical foundations. These bonds are essential for institutions pursuing bold digital ventures that require harmonized technological growth. Architectural choices carry weighty implications for financial health, regulatory standing, and innovation across departmental lines. Technical experts and senior officials gain clarity by recognizing how these concepts stretch beyond technical frameworks to address vital institutional needs and elevate market competitiveness. Through a coherent blueprint, enterprise architecture supports steady technological strides alongside operational alignment, nurturing resilience in fluctuating conditions.